Fattening sheep behavior established within herbaceous system and pear trees (Pyrus communis) (Revista Sistemas de Producción Agroecológicos, 2015)
Due to the popular belief that sheep can be predators of fruit trees, producers of pear (Pyrus communis) in Colombia, is not use their herbaceous stratum as grazing. This work demonstrated that is possible to graze those areas in an integrated system (agrosilvopastoral system) without risk to the pear trees, while that obtained good weight gain and weeds spontaneous was controlled.
Keywords: silvopasture; fruit; sheep; pears